2016
DOI: 10.1371/journal.pone.0168438
|View full text |Cite
|
Sign up to set email alerts
|

Shape Variation in Neotropical Cytheridella (Ostracoda) Using Semilandmarks-Based Geometric Morphometrics: A Methodological Approach and Possible Biogeographical Implications

Abstract: Geometric morphometrics offer effective methods to obtain information about shape and shape variability. In ostracodology, landmark-based methods are, however, not well established. To test the applicability of geometric morphometric analyses for ostracods, we investigated shape variation among recent and fossil populations of the genus Cytheridella using a combination of landmarks and semilandmarks. The study focuses on the species' intraspecific morphological variability on a supra-regional scale, comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…We applied the geometric morphometrics semilandmark-based approach [ 43 , 44 , 45 , 46 , 47 , 48 , 49 ] to describe the overall shape variation of head and pronotum. The software tpsDig v2.31 [ 50 ] and tpsUtil v1.76 [ 51 ] ( ) were used to define the point configurations ( Figure 1 c,d) of the head (N H = 13) and pronotum (N P = 22).…”
Section: Methodsmentioning
confidence: 99%
“…We applied the geometric morphometrics semilandmark-based approach [ 43 , 44 , 45 , 46 , 47 , 48 , 49 ] to describe the overall shape variation of head and pronotum. The software tpsDig v2.31 [ 50 ] and tpsUtil v1.76 [ 51 ] ( ) were used to define the point configurations ( Figure 1 c,d) of the head (N H = 13) and pronotum (N P = 22).…”
Section: Methodsmentioning
confidence: 99%
“…Right and left valves were investigated separately due to 15 dimorphism in size and shape (Wrozyna et al, 2014). Beyond that, females and males were analyzed separately because a large part of within-valve variation has been shown to depend on sexual differences (such as the presence of brood pouches in females; Wrozyna et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Carapace outline was defined by two curves between LM 7 and 8, each comprising 30 equidistantly spaced semilandmarks ( Fig. 2; see also Wrozyna et al, 2016).…”
Section: Generalized Procrustes Analysismentioning
confidence: 99%
“…Both shortened and elongated morphotypes co-occur in one lake (i.e. Punta Laguna) (Wrozyna et al, 2018a). On the one hand, this co-occurrence could suggest the presence of microhabitats with specific environmental conditions, suggesting different impacts on valve calcification in the very same ecosystem.…”
Section: Genetic Diversity or Ecophenotypic Plasticity?mentioning
confidence: 99%
“…The subject of study is the valves of the Neotropical cytheroidean ostracod species, Cytheridella ilosvayi. Studies by von Daday (1905) and Wrozyna et al (2016Wrozyna et al ( , 2018a already demonstrated considerable biogeographical variation in valve morphology among Floridian, Mexican, and Brazilian populations of that species. Morphological differences in populations of C. ilosvayi are discernible in both valves and appendages, adult and juvenile (A-1 to A-3) stages, and across sexes, suggesting that morphological divergence is a result of long-term biogeographic isolation (Wrozyna et al, 2018b).…”
mentioning
confidence: 93%